Self-Fulfilling Risk Predictions : An Application to Speculative Attacks - Flood, Robert (IMF Working Papers; Working Paper, 1998)
The paper shows that changing market beliefs about currency risk can generate a self-fulfilling speculative attack on a fixed exchange rate. The attack does not require a later change in policies to make it profitable. This is illustrated by introducing an endogenous risk premium into a 'first-generation model' of a speculative attack. The model is further modified to take account of sterilization, debt-financed fiscal deficits, and anticipatory price-setting behavior. The model is used to interpret the 1994 Mexican peso crisis.